Bionic women and men ‐ Part 2: Arterial stiffness in heart failure patients implanted with left ventricular assist devices. Issue 5 (22nd April 2020) - McDonnell, Barry J.; Rosenblum, Hannah; Cornwell, William K.; Kanwar, Manreet; Cockcroft, John R.; Stöhr, Eric J.
Abstract : New Findings: What is the topic of this review? This review discusses how implantation of continuous flow left ventricular assist devices impact arterial stiffness and outcome. What advances does it highlight? Not all patients implanted with continuous flow left ventricular assist devices show an increase in arterial stiffness. However, in those patients where arterial stiffness increases, levels of composite outcome (stroke, gastrointestinal bleeding, pump thrombosis and death) is significantly higher than those who's arterial stiffness does not increase. Abstract: In parallel with the major advances in clinical care, technological advancements and implantation of mechanical circulatory support in patients with severe heart failure have resulted in these patients living longer. However, these patients are still at increased risk of stroke and gastrointestinal bleeding. The unique continuous flow produced by various left ventricular assist devices (LVADs) has been suggested as one potential reason for this increased risk of stroke and gastrointestinal bleeding. Furthermore, these continuous‐flow (CF) devices challenge our understanding of circulatory blood pressure and flow regulation in relationship to organ health. In healthy pulsatile and dynamic systems, arterial stiffness is a major independent risk factor for stroke. However, to date, there are limited data regarding the impact of CF‐LVAD therapy on arterial stiffness. The purpose of this report is to discuss the variable impact of CF‐LVAD therapy on arterial stiffness and attempt to highlight some potential mechanisms linking these associations in this unique population. Abstract :